Efektivitas Layanan Informasi dengan Teknik Discovery Learning dalam Meningkatkan Perencanaan Karier Siswa di SMA Muhammadiyah Labuan - Siti Malihah; Vasco Delano; Devi Nurul Fikriyani (JCOSE Jurnal Bimbingan dan Konseling, 2026)
Career iplanning iis ian iessential ipart iof iadolescent idevelopmental itasks. iHowever, imany istudents istill iface idifficulties, iespecially iat ithe iend iof itheir ischooling iwhen ithey ineed ito iprepare ifor itheir ifuture. iThis istudy iaims ito iexamine ithe ieffectiveness iof iinformation iservices iusing ithe iDiscovery iLearning itechnique iin iimproving ithe icareer iplanning iof itenth-grade istudents iat iSMA iMuhammadiyah iLabuan iin ithe i2025/2026 iacademic iyear. iThis iresearch iemployed ia iquasi-experimental imethod iwith ia iNon-equivalent iPretest-Posttest iControl iGroup idesign. iThe iresearch isubjects iconsisted iof i30 itenth-grade istudents idivided iinto itwo igroups: ithe iexperimental igroup iand ithe icontrol igroup, ieach iconsisting iof i15 istudents icategorized ias ihaving ilow ilevels iof icareer iplanning. iThe iresearch iinstrument iwas ia icareer iplanning iquestionnaire. iThe iintervention, inamely iinformation iservices iusing ithe iDiscovery iLearning itechnique, iwas iconducted iin isix isessions iaccording ito ithe icounseling iteacher’s ischedule iat ischool. iData iwere ianalyzed iusing ithe iWilcoxon iSigned iRanks iTest iand ithe iMann-Whitney iU iTest. iThe iWilcoxon itest iresults ishowed ia isignificant idifference ibetween ipretest iand iposttest iscores iin ithe iexperimental igroup iwith ia ivalue iof iAsymp. iSig. i(2-tailed) i= i0.001 i< i0.05, iindicating ithat ithe iintervention ihad ia isignificant ieffect ion iimproving istudents’ icareer iplanning. iThe icontrol igroup ialso ishowed ia idifference ibetween ipretest iand iposttest iscores iwith ia ivalue iof iAsymp. iSig. i(2-tailed) i= i0.001 i< i0.05, ibut ithe iimprovement iwas inot ias isubstantial ias ithat iof ithe iexperimental igroup. iFurthermore, ithe iMann-Whitney iU iTest iresult iobtained ian iAsymp. iSig. i(2-tailed) i= i0.004 i< i0.05, iindicating ia isignificant idifference ibetween ithe iposttest iresults iof ithe iexperimental iand icontrol igroups. iThus, iit ican ibe iconcluded ithat iinformation iservices iusing ithe iDiscovery iLearning itechnique iare ieffective iin iimproving ithe icareer iplanning iof itenth-grade istudents iat iSMA iMuhammadiyah iLabuan iin ithe i2025/2026 iacademic iyear.